2022
DOI: 10.1038/s41593-022-01011-x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal relations in the mouse brain revealed by single-cell and spatial transcriptomics

Abstract: The mammalian brain contains many specialized cells that develop from a thin sheet of neuroepithelial progenitor cells. Single-cell transcriptomics revealed hundreds of molecularly diverse cell types in the nervous system, but the lineage relationships between mature cell types and progenitor cells are not well understood. Here we show in vivo barcoding of early progenitors to simultaneously profile cell phenotypes and clonal relations in the mouse brain using single-cell and spatial transcriptomics. By recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 66 publications
(87 reference statements)
6
58
0
Order By: Relevance
“…Our findings indicate that some individual microglia undergo mass expansion as evidenced by the clouds of sparse-labelled microglia at P30. This finding is in line with a recent study where in vivo barcoding was used to track clonal expansion of various cell types, including microglia, within the embryonic brain (Ratz et al, 2022). In line with our findings, this study showed that expanded microglial progenitors span anatomical niches in an almost continuum (Ratz et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings indicate that some individual microglia undergo mass expansion as evidenced by the clouds of sparse-labelled microglia at P30. This finding is in line with a recent study where in vivo barcoding was used to track clonal expansion of various cell types, including microglia, within the embryonic brain (Ratz et al, 2022). In line with our findings, this study showed that expanded microglial progenitors span anatomical niches in an almost continuum (Ratz et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with a recent study where in vivo barcoding was used to track clonal expansion of various cell types, including microglia, within the embryonic brain (Ratz et al, 2022). In line with our findings, this study showed that expanded microglial progenitors span anatomical niches in an almost continuum (Ratz et al, 2022). Here we examined the changes in the spatial distribution of sparsely labelled microglia, which were highly clustered during embryonic development in comparison to adulthood, when the labelled microglia were more randomly distributed with a lower NND in line with the formation of the mosaic similar to the trends observed in the total PU.1 + population.…”
Section: Discussionsupporting
confidence: 90%
“…Timelapse microscopy studies conducted in cerebral organoids have demonstrated that the characteristic behaviors of radial glia subtypes are recapitulated in organoids [ 95 , 96 ], as well as their capacity to differentiate via direct and indirect neurogenesis [ 97 ]. In addition to timelapse microscopy, technologies that enable multiplexed tracking of cell lineage at high-throughput using single cell transcriptomics can be applied to cerebral organoids [ 98 , 99 ] and primary tissue [ 79 , 100 , 101 ]. Examining mechanisms underlying human brain development using brain organoids will critically depend on rigorous benchmarking of the differentiation trajectories of neural progenitor cells.…”
Section: Benchmarking Against Primary Tissuementioning
confidence: 99%
“…Spatial omics technologies map out organizational structures of cells along with their genomics, transcriptomics, proteomics and epigenomics profiles, providing powerful tools for deciphering mechanisms of functional and spatial arrangements in normal development and disease pathology (Larsson et al 2021;Longo et al 2021;Marx 2021;Deng et al 2022;Dhainaut et al 2022;Ratz et al 2022;Zhao et al 2022). The collection of available approaches provides a wide spectrum of throughput and spatial resolution.…”
Section: Introductionmentioning
confidence: 99%